Human detection and depth calculation using stereographic vision with pixel disparity and HOG classifier - Tejasri, Vemuri; Ravi Babu, D.; N.V. Satyanarayana, K.; Srinivas Reddy, D.; Shiva Shankar, R. (International Journal of Engineering and Technology, 2019)
Mainly image processing is used for detection of objects with feasible number of constraints with different detection meth-odologies is defined used by camera-based detection. This method is used to find correspondence with respect to different objects. So that, in this paper, we propose Novel and simple method which is worked based on different region of interests present in video or image. This method mainly worked based on Histogram Oriented Gradients in image processing events. Our method also uses filtering approach with sequential data presentation to access interested data from image or video. Our experimental results mainly show effective visualization results with respect to different selection of regions.Â Â Â